Some features of the trial of adoption (adrogation) of a child in the courts of the Republic of Kazakhstan - Aliyeva, L.R. (Bulletin of the Karaganda University “Law Series”, 2022)
Within the framework of this research, some issues of the trial of the adoption (adrogation) of a child arising in the courts of the Republic of Kazakhstan are considered. The authors analyze the composition of persons participating in a case about adoption (adrogation) of a child in civil proceedings. Two main categories of subjects are considered, depending on the obligation of their participation in the trial in the consideration and resolution of civil cases about the adoption (adrogation) of a child provided for in domestic national legislation. A comparative analysis of similar provisions of legislation of the Russian Federation and Ukraine has also been carried out. Attention is drawn to various scientific views available in doctrine sources on the issues under consideration. The authors take into account that, at the moment, there is a certain inconsistency in the norms of domestic legislation on some issues relating to the trial of the adoption (adrogation) of a child. An analysis of legal norms regulating the procedure for consideration of cases of adoption (adrogation) of a child in the courts of the Republic of Kazakhstan is carried out. The methodological basis of this scientific work is dialectical, systemic, comparative-legal, regulatory, and other methods of knowledge. The norms of the main international legal acts governing this sphere of relations are taken into account. The issue of the importance of obtaining the consent of a child to be adopted is also considered in the article. The possibility of compulsory participation in the case of adoption (adrogation) of a child of teachers and psychologists, as well as the child who has reached the age of 10 years, has been considered. As part of the improvement of domestic law regulating the attitudes in the sphere of adoption (adrogation) of children in the Republic of Kazakhstan, it is proposed to solve certain problems arising in the process of consideration of civil cases about the adoption (adrogation) of the child.